Adaptive learning concept selection: a bibliometric review of scholarly literature from 2011 to 2019 (Educational Dimension, 2023)
The article describes the bibliometric analysis of scientific literature on adaptive learning in social sciences. With the selected documents, a cluster analysis was carried out according to the co-occurrence of keywords. As a result, the keywords were divided into five clusters, including ones associated with computer-aided instruction, engineering education, basic didactic principles, and individualized learning. The most interrelated keywords, primary keywords, and the chronological limits of the research were also determined from 2011 to 2019.
Keywords: adaptive learning; bibliometric review; VOSviewer